Jaunas plaša patēriņa preces ieviešana tirgū - Kriķis, Uģis (Latvijas Universitāte, 2009)
Bakalaura darba tēma ir „Jaunas plaša patēriņa preces ieviešana tirgū”. Bakalaura darba mērķis ir izpētīt zinātnisko literatūru un, pamatojoties uz iegūtajām zināšanām, analizēt uzņēmuma Henkel darbību jauna produkta izstrādes un tirgū ieviešanas procesā, kā arī izstrādāt priekšlikumus uzņēmuma efektīvai rīcībai nākotnē. Bakalaura darbs sastāv no 3 nodaļām. Darba apjums ir 69. lappuses, ietverti 26 attēli un 2. tabulas. Darba teorētiskajā daļā ir izpētīta mārketinga zinātniskā literatūra par jauna produkta būtību, tā izstrādi un virzīšanu tirgū, kā arī par mārketinga komunikācijas instrumentiem jauna produkta virzīšanai tirgū. Bakalaura darba otrajā nodaļā darba autors analizē sadzīves ķīmijas nozīmi Baltijas valstu tirdzniecībā, izpēta konkurenci Latvijā un aplūko Henkel darbības mērķus un panākumus. Pēdējā nodaļā tiek analizēts Henkel jaunā produkta Bref Tornado izstrādes process un izmantotie mārketinga instrumenti produkta virzīšanai tirgū. Darba noslēgumā autors, balstoties uz izpētīto zinātnisko literatūru, statistisko, ekonomisko un uzņēmuma iekšējo datu pamata, izdarījis secinājumus un izstrādājis priekšlikumus uzņēmumam Henkel, kas uzlabotu uzņēmuma turpmāko jauno produktu izstrādi.

The topic of the bachelor’s thesis is the “Introduction of a new consumer article into a market”. The aim of the bachelor’s thesis has been to examine the scientific literature and on the basis of the knowledge obtained to produce the analysis of the operations of the company Henkel during the process of the elaboration and production of a new product and the introduction of this product into a market as well as to present the recommendations for the effective operations of the company in the future. The bachelor’s thesis consists of 3 chapters. The volume of the thesis amounts to 69 pages with 26 pictures and 2 tables. In the theoretical part of the thesis the author has examined the scientific literature on marketing devoted to the essence of a new product, its development and promotion in a market as well as the tools of the marketing communications for the promotion of a new product in a market. In the second chapter of the bachelor’s thesis the author the thesis has provided the analysis of the household chemical products in the sales of the Baltic States, explored the competition in Latvia and considered the aims of the operations by the Henkel and its progress. In the last chapter the author has analyzed the process of the development of Bref Tornado, the new product by Henkel, and the marketing tools used to promote this product in the market. In the conclusion of the thesis the author on the basis of the scientific literature examined, the statistical, economic and internal company data has produced the conclusions and presented the proposals for the Henkel which would improve the future development of the new products.
Introduction of new consumer article into a market
Keywords: Vadībzinātne